2021
DOI: 10.1186/s12884-021-04220-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends of maternal health service coverage in the Democratic Republic of the Congo: a pooled cross-sectional study of MICS 2010 to 2018

Abstract: Background Maternal health services are essential for reducing maternal and newborn mortality. However, maternal health service status in the Democratic Republic of the Congo (DRC) remains poorly understood. This study aims to explore the trends of antenatal care (ANC) and skilled birth attendance coverage in the past decade in the DRC. Methods The 13,361 participants were from two rounds of Multiple Indicators Cluster Survey (MICS) conducted by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Indeed, previous studies reported that maternal mortality ratio (MMR) in the DRC was very high, and it was estimated at 473 maternal deaths per 100 000 live births. 57 This is alarming because it also means that the country won’t reach the SDG 3.1 aimed at reducing, by 2030, the MMR at 70 maternal deaths per 100 000 live births. Yet, obstetrical complications such as bleeding, eclampsia, sepsis and unsafe abortions, accounting for nearly 80% of the MMR cases require urgent and appropriate care through health insurance coverage as a pathway to access affordable healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies reported that maternal mortality ratio (MMR) in the DRC was very high, and it was estimated at 473 maternal deaths per 100 000 live births. 57 This is alarming because it also means that the country won’t reach the SDG 3.1 aimed at reducing, by 2030, the MMR at 70 maternal deaths per 100 000 live births. Yet, obstetrical complications such as bleeding, eclampsia, sepsis and unsafe abortions, accounting for nearly 80% of the MMR cases require urgent and appropriate care through health insurance coverage as a pathway to access affordable healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have policy and programmatic implications in the DRC given the low coverage in health insurance, and they might explain the poor quality of maternal and child health indicators in the DRC. Indeed, previous studies reported that maternal mortality ratio (MMR) in the DRC was very high, and it was estimated at 473 maternal deaths per 100 000 live births 57. This is alarming because it also means that the country won’t reach the SDG 3.1 aimed at reducing, by 2030, the MMR at 70 maternal deaths per 100 000 live births.…”
Section: Discussionmentioning
confidence: 99%
“…This study took place in Lubumbashi city, the third-largest city in the DRC, with an area of 747 km² and an estimated population of over 2 million inhabitants in 2016 and an average density of 2807 inhabitants per km² 21. In urban areas, such as Lubumbashi, the health system is characterised by an increasing number of health facilities in the poorly regulated private sector country 24 25. More than 90% of the population pays out of pocket to access basic and emergency obstetric and neonatal care, with the consequences of catastrophic expenditure for households and exacerbation of poverty 26…”
Section: Methodsmentioning
confidence: 99%
“…Coverage of outpatient PNC consultations reached 12% for newborns and 7% for mothers 27. The maternal mortality ratio is high and estimated at 473/100 000 live births 28. Due to ongoing conflicts, maternal healthcare coverage is unstable and deteriorating in several regions, hampering overall progress in maternal health outcomes in the country 24 25…”
Section: Methodsmentioning
confidence: 99%
“…The high MMR in Africa is affected by various factors, such as health expenditure, the availability and quality of maternal health services, and maternal health-seeking behaviours (MHSB) [ 5 , 6 ]. MHSB is defined as the utilization of maternal health services by pregnant individuals to ensure the health of themselves and their unborn children during pregnancy, childbirth, and the postpartum period [ 2 , 7 ].…”
mentioning
confidence: 99%